Association of Programmed Death 1 Protein Ligand (PD-L1) Expression With Prognosis in Merkel Cell Carcinoma - Hanna, Glenn J.; Kacew, Alec J.; Tanguturi, Anusha R.; Grote, Hans J.; Vergara, Victoria; Brunkhorst, Beatrice; Rabinowits, Guilherme; Thakuria, Manisha; LeBoeuf, Nicole R.; Ihling, Christian; DeCaprio, James A.; Lorch, Jochen H. (Frontiers in Medicine, 2020)
Background: Merkel cell carcinoma (MCC) is a rare neuroendocrine skin cancer. Prior to the advent of immunotherapy, treatment options were limited. In our study, we evaluate the impact of tumor cell PD-L1 expression and tumor immune microenvironment on survival in MCC patients who were not treated with immune checkpoint inhibitors. Methods: Clinical data and tissue samples were collected from 78 patients with confirmed MCC treated at Dana-Farber Cancer Institute. Specimens were analyzed for the distribution of PD-L1 by immunohistochemistry staining (IHC) and standardized analysis. Results were correlated with survival data. Results: In this study, membrane and cytoplasmic MCC tumor cell staining for PD-L1 was detected in 22.4% (15 of 67) of cases and PD-L1 staining of intratumoral microvessels and PD-L1 positive immune cells at the infiltrative margins of the tumor in 92.5% (62 of 67) of cases. In patients untreated with immune checkpoint inhibitors, median overall survival was not different for patients based on PD-L1 expression (PD-L1+ 64 months vs. PD-L1- not reached; HR= 1.26, 95% CI: 0.46-3.45; p= 0.60). Conclusion: PD-L1 expression is frequently detected in MCC tumor cells and tumor microenvironment. PD-L1 expression did not affect prognosis in this cohort that had not received PD-1/L1 blockade.